Business data networks and security - Panko, Raymond R.; Panko, Julia L. (Always learning, 2015)
Business Data Networks and Security guides readers through the details of networking, while helping them train for the workplace. It starts with the basics of security and network design and management; goes beyond the basic topology and switch operation covering topics like VLANs, link aggregation, switch purchasing considerations, and more; and covers the latest in networking techniques, wireless networking, with an emphasis on security. With this text as a guide, readers learn the basic, introductory topics as a firm foundation; get sound training for the marketplace; see the latest advances in wireless networking; and learn the importance and ins and outs of security.